Overlooked and Invisible: A Profile of the Japanese Educated Working Poor - Stiefenhofer, Pascal (Advances in Social Sciences Research Journal, 2023)
Expanding the work proposed by Murakami et al. (2011), we seek to discover and profile a subset of the Japanese working poor, namely those who are educated to degree level. Using data from the Japanese Household Panel Survey, we build up a profile into the educated working poor, and show they have significantly lower self-reported levels of income satisfaction and life satisfaction. Further, we explore the extent to which geographical factors play a key role in explaining the newly identified educated working poor, and find that there are significant spatial differences in the poor rate, and that job location, occupation, and firm size is significantly different for the educated working poor compared to the working poor.